2001
DOI: 10.1046/j.1464-5491.2001.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited impact of lifestyle education in patients with Type 2 diabetes mellitus and microalbuminuria: results from a randomized intervention study

Abstract: Despite the many resources invested in behaviour modification in this study, only modest changes were obtained in nutrient intake. Further studies are required to determine the best method of inducing long-lasting changes in behaviour in Type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 21 publications
0
50
0
1
Order By: Relevance
“…24,25 In addition, there was a large variation in intervention intensity. For example, Christian and colleagues 13 described an intervention in which patients only had a pre-intervention visit in addition to usual care, where a computer-based lifestyle assessment took place.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 In addition, there was a large variation in intervention intensity. For example, Christian and colleagues 13 described an intervention in which patients only had a pre-intervention visit in addition to usual care, where a computer-based lifestyle assessment took place.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Follow-up duration ranged from six weeks 12 to 3.8 years. 24 In two of the studies, patients' usual healthcare providers were involved; 13,21 in four studies, the interventionist was a PhD student or researcher [16][17][18]21 and in other studies healthcare professionals (eg nurses and dietitians) implemented the intervention. The intervention described by Christian and colleagues took place during usual care, after the computer-based lifestyle and motivational assessment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The success of permanent lifestyle changes is dependent on patients' degree of motivation, psychosocial condition, risk profile and compliance: patient nonadherence to the lifestyle regimen is the most common barrier to care. 29,30 Further studies are required to determine the best process for inducing long-lasting change in behaviour in type 2 diabetic patients. The Diabetes Control and Complications Trial, which studied intensive management of type 1 diabetes, also reported post-intervention worsening, but this occurred 4 years after the intervention.…”
mentioning
confidence: 99%
“…These results underline the importance of close follow-up organized around a multidisciplinary team that provides comprehensive and shared care. 30,32,33 We may conclude that patients adhered to the program as long as they were being "coached. "…”
mentioning
confidence: 99%
“…A significantly larger decline in the ratio of daily intake of saturated and unsaturated fatty acids occurred at both the 4-and 8-year examinations in the intervention group, but otherwise there were no significant differences in lifestyle performance between the two groups, despite the many resources spent on intensive behavior modification (16). In contrast, a marked effect was seen on other risk factors.…”
Section: Intensified Multifactorial Intervention In Type 2 Diabetesmentioning
confidence: 80%